Counseling on The Prevention of Tuberculosis Transmission at Pagar Merbau Health Center - Gurusinga, Rahmad (JURNAL PENGMAS KESTRA (JPK), 2023)
Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium tuberculosis. TB infection usually attacks the lungs, but can also affect other body organs such as the kidneys, brain or bones. TB bacteria spread through the air when an infected person coughs or sneezes, and other people can become infected by inhaling the bacteria. Preventing the transmission of tuberculosis (TB) is an important effort to control the spread of the disease, therefore early diagnosis and treatment of TB is very necessary to prevent further transmission and avoid serious complications. The aim of implementing this outreach is to increase the knowledge of TB sufferers regarding how TB is transmitted so that sufferers can be aware of the environment. The method in community service was carried out with a pretest before counseling and a posttest after counseling. Community service was carried out at the Pagar Merbau Community Health Center, Deli Serdang Regency with a total of 32 participants. From the results of activities before counseling was carried out on preventing TB transmission, only 55% of participants had good knowledge and after the counseling was carried out the majority had good knowledge, reaching 95%. It can be concluded that it is important to know how TB disease is transmitted, so that patients or families can anticipate their health, especially regarding TB disease because TB disease can easily be transmitted to other people.